2018
DOI: 10.1039/c8fo01429a
|View full text |Cite
|
Sign up to set email alerts
|

Roasting improves the hypoglycemic effects of a large-leaf yellow tea infusion by enhancing the levels of epimerized catechins that inhibit α-glucosidase

Abstract: Teas contain bioactive polyphenols, such as (-)-epigallocatechin gallate (EGCG), which is not stable during the processing of tea. EGCG can be epimerized into (-)-gallocatechin gallate (GCG), which is present in very small amounts in fresh tea leaves. An infusion made from roasted large-leaf yellow tea inhibited α-glucosidase more significantly than an infusion of unroasted yellow tea, with IC50 values of 76.08 ± 8.96 and 170.17 ± 33.00 μg mL-1, respectively. After roasting, the content of GCG showed about a 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…GCG‐rich catechins were more effective than EGCG‐rich catechins in lowering blood cholesterol and triacylglycerol levels as well as in lowering postprandial blood glucose after consuming starch. [ 17,43 ] Catechin polymers, formed under the high temperature conditions, may also contribute to the activities of YTE; several reports showed that catechin dimers theaflavins lowered body lipid in obese rat, [ 44 ] and theaflavin‐enriched black tea extract protected against obesity‐related inflammation in the obese ZDF rat model. [ 45 ] Careful studies on the active compounds in YTE for the induction of thermogenesis are essential for elucidating the detailed mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GCG‐rich catechins were more effective than EGCG‐rich catechins in lowering blood cholesterol and triacylglycerol levels as well as in lowering postprandial blood glucose after consuming starch. [ 17,43 ] Catechin polymers, formed under the high temperature conditions, may also contribute to the activities of YTE; several reports showed that catechin dimers theaflavins lowered body lipid in obese rat, [ 44 ] and theaflavin‐enriched black tea extract protected against obesity‐related inflammation in the obese ZDF rat model. [ 45 ] Careful studies on the active compounds in YTE for the induction of thermogenesis are essential for elucidating the detailed mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%
“…Using mature fresh tea leaves with stems in the summer and autumn through mechanical harvest and process to yield the final product of YT. [ 17 ] Second, there are two special steps called “sealed yellowing” and “roasting” in the manufacturing process to produce roasted and caramel aromas and flavors similar to coffee and cocoa. The light fermentation and seal turn the leaves to a yellow color, while high‐temperature roasting (140–150 °C for 15 min) brings forth the brown color and the slightly astringent taste of the final YT product.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yellow tea could ameliorate glucose intolerance and insulin resistance without dose dependence [70]. Further, the roasted yellow tea could improve insulin sensitivity and reduce fasting blood sugar due to the strong affinity of GCG to target protein-glycosidase, and the strong inhibition effect of GCG on α-glucosidase activity [71].…”
Section: Experimental Studiesmentioning
confidence: 99%